Fatty acid metabolism: A new therapeutic target for cervical cancer - Ping, Pengbin; Li, Juan; Lei, Hongbin; Xu, Xiaoying (Frontiers in Oncology, 2023)
Cervical cancer (CC) is one of the most common malignancies in women. Cancer cells can use metabolic reprogramming to produce macromolecules and ATP needed to sustain cell growth, division and survival. Recent evidence suggests that fatty acid metabolism and its related lipid metabolic pathways are closely related to the malignant progression of CC. In particular, it involves the synthesis, uptake, activation, oxidation, and transport of fatty acids. Similarly, more and more attention has been paid to the effects of intracellular lipolysis, transcriptional regulatory factors, other lipid metabolic pathways and diet on CC. This study reviews the latest evidence of the link between fatty acid metabolism and CC; it not only reveals its core mechanism but also discusses promising targeted drugs for fatty acid metabolism. This study on the complex relationship between carcinogenic signals and fatty acid metabolism suggests that fatty acid metabolism will become a new therapeutic target in CC.